Electrochemical reduction of CO2 at metal-free N-functionalized graphene oxide electrodes. (20th August 2018) - Yuan, Jing; Zhi, Wen-Ya; Liu, Li; Yang, Man-Ping; Wang, Huan; Lu, Jia-Xing
Abstract: Exploring metal-free catalysts for electroreduction of CO2 into value-added fuels has been a crucial challenge in nowadays society. Herein we report some metal-free electrocatalysts for electrocatalytic reduction of CO2 to liquid products, such as ethanol and acetone. We develop functionalized graphene oxide (GO) surfaces with five pyridine derivatives: pyridoxine, 4-hydroxypyridine, 4-aminopyridine, 8-hydroxyquionline, and 5-amino-1, 10-phenanthroline. Remarkably, pyridoxine modified on GO sheets with the pyridinic N content of 2.32% shows the optimum catalytic ability for electrochemical reduction of CO2, and the overall faradaic efficiency reaches up to 45.8%. Besides, other four pyridine derivatives functionalized GO exhibit various abilities for CO2 reduction to ethanol and acetone. The experimental results show that N-doping can alter the electronic properties of GO for enhancing the catalytic active for CO2 electroreduction, which is closely associated with the content of modified pyridinic N and the special structure of modified pyridine derivatives. Our work may provide inventive thought to design metal-free electrocatalysts for CO2 reduction to useful chemical fuels. Graphical abstract: In our work, we systematically and carefully synthesized a series of metal-free electrocatalysts, i.e., pyridoxine functionalized graphene oxide (GO-VB6 ), which present high catalytic active for electroreduction of CO2 to ethanol. Besides, other four pyridine derivatives (4-hydroxypyridine, 4-aminopyridine, 8-hydroxyquionline, and 5-amino-1, 10-phenanthroline) functionalized GO were also successfully synthesized and exhibit various catalytic abilities for CO2 reduction. Image 1